1995
DOI: 10.1007/bf01839298
|View full text |Cite
|
Sign up to set email alerts
|

The concentration of ionized magnesium in serum during the periparturient period of non-paretic dairy cows

Abstract: Ion-selective electrodes have recently been designed for determining the ionized concentration of magnesium (Mg2+) in serum. This development may allow new insights into some metabolic diseases of cattle. For this report, the concentrations of Mg2+, total magnesium (Mgtot), ionized calcium (Ca2+), total calcium (Catot), and inorganic phosphate (P(i)) were determined in sera from seventeen 3- to 16-year-old Brown Swiss and crossed Simmental/Red Holstein cows during the periparturient period. In each animal, a t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
19
0
2

Year Published

1996
1996
2017
2017

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 25 publications
3
19
0
2
Order By: Relevance
“…Magnesium has no effect on hemostasis when serum levels are less than 3 mM but the coagulation time of whole blood is prolonged when Mg concentration are greater than 7 mM [12]. The total Mg level found in this study for bovine serum was 0.93 ± 0.18 mM/l which is similar to other reports [4,15,18]. However, the Mg content in FF (S) showed a significant high level compared with the value in plasma and the Mg level decreased with follicle development with approximately sera being reached in the largest follicles.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…Magnesium has no effect on hemostasis when serum levels are less than 3 mM but the coagulation time of whole blood is prolonged when Mg concentration are greater than 7 mM [12]. The total Mg level found in this study for bovine serum was 0.93 ± 0.18 mM/l which is similar to other reports [4,15,18]. However, the Mg content in FF (S) showed a significant high level compared with the value in plasma and the Mg level decreased with follicle development with approximately sera being reached in the largest follicles.…”
Section: Discussionsupporting
confidence: 81%
“…The Gladependent Ca binding is a prerequisite for the interaction between these coagulation factor proteins and biological membranes [23]. In this study, total serum Ca concentration were similar to those closely previously reported [4,16,18,19,22] as were the ionized Ca concentration [11,19]. The ionized Ca concentration in FF was found relatively constant at all stages of follicles and approximated the bovine serum level.…”
Section: Discussionsupporting
confidence: 73%
“…The measured strong ion difference obtained from 7 strong ions34 (SID 7 , mEq/L) was calculated by the measured value for [Ca 2+ ] determined by ion‐selective potentiometry and assigning a charge of +1.38 to magnesium assuming 69% dissociation35 and −1 to D‐lactate and L‐lactate assuming 100% dissociation such that:…”
Section: Methodsmentioning
confidence: 99%
“…The chemical gradient from 2-4 mM in the lumen, of which 49-100 % is ultrafilterable (Storry, 1961), to 0.8-1*2 mM in blood serum (Moodie, 1975), of which about 70°% is ionized (Riond, Kocabagli, Spichiger & Wanner, 1995), is opposed by a transruminal potential difference of about 30 mV (blood side positive, Dobson & Phillipson, 1958) that overcomes the chemical driving force. Magnesium net absorption across the rumen epithelium is therefore mainly driven by active transport mechanisms (Martens, Harmeyer & Breves, 1976).…”
Section: Introductionmentioning
confidence: 99%